Paying For Pollution: Carbon Tax as A Mitigation for Carbon Emission Problem - Kenley Maccauley Riyono; Luky Patricia Widianingsih (Universitas Pendidikan Ganesha, 2024)
There is a need to evaluate the effectiveness of carbon tax policies across different sectors in reducing emissions and increasing government revenue, while assessing their practical implementation and impact on economic and environmental outcomes. This study aims to determine the effectiveness of carbon tax implementation in various sectors and whether it can reduce carbon emissions and increase government revenue, thereby helping to mitigate climate change and improve environmental, social, and economic conditions. The sample in this study includes 24 countries that have implemented a carbon tax, allowing for the analysis of carbon emissions levels and government revenue indices. Regression analysis is used to determine the strength of the relationship between carbon tax implementation in various sectors, the share of jurisdiction emissions covered, and government revenue. The results indicate that implementing a carbon tax in various sectors significantly reduces carbon emissions and increases government revenue. These findings suggest that a carbon tax is essential as an environmental policy in all countries and represents the most effective way to mitigate carbon emissions. This evidence should be considered by countries contemplating its implementation.